Immune response to racotumomab in a child with relapsed neuroblastoma - Sampor, Claudia (2012)
Immunotherapy targeting ganglioside antigens is a powerful tool for the treatment of high risk neuroblastoma. However, only treatment with anti-GD2 antibodies has been used in clinical practice and other options may be pursued. We report the use of racotumomab, an anti-idiotype vaccine against N-glycolyl neuraminic acid (NeuGc)- containing gangliosides, eliciting an immune response in a child with relapsed neuroblastoma expressing the NeuGcGM3 ganglioside.